Deteksi Dini Anemia pada Remaja dengan Pemeriksaan Hemoglobin (HB) pada Siswa SMA Negeri 1 Manganitu - Kasaluhe, Meityn Disye; Hinonaung, Jelita Siska Herlina; Gansalangi, Ferdinand; Mahihody, Astri Juwita (Civiliza Publishing, 2024)
Adolescence is a transition period from childhood to adulthood. The age range of adolescence is 10-18 years. At this age, various physical, biological and psychological changes can occur rapidly. One of the developments experienced especially in adolescent girls is menstruation. Menstruation is the process of shedding the inner layer of the female uterine wall (endometrium) which contains many blood vessels. The menstrual cycle that occurs causes adolescent girls to have a higher risk of experiencing anemia compared to adolescent boys. In adolescents, anemia will greatly affect academic achievement at school due to decreased motor activity, decreased endurance and decreased concentration of adolescents in learning. The purpose of this Community Service is to detect anemia in adolescents early. The method consists of initial exploration and survey, coordination of implementation plans, implementation, and evaluation. The results of this community service are an increase in participant scores after being given education about anemia. In addition, the results of hemoglobin (Hb) level examinations in 88 students showed that most students of SMA N 1 Manganitu were included in the normal category. Students with low hemoglobin (Hb) levels numbered 14 (16%). By implementing education about anemia, students' knowledge about anemia has increased. In addition, examination of hemoglobin (Hb) levels in students provides information about the incidence of anemia in students at SMA Negeri 1 Manganitu.